(untitled) (International Research Journal of Religious Studies, 2021)
To get know how about the compilation of the Quran. Quran was revealed gradually in 23 years. Prophet Muhammad (PBUH) was very vigilant and keen about collecting and preserving the Holy Quran. Prophet Muhammad used to call sahabah and order them to write down verses. Then he orders them to recite the written verses as a cross check to remove any mistake. In this way the Quran verses became saved. The idea of a compilation of the Quran originated when a significant in a battle during the rule of Hazrat Abu Bakar Siddique.Muslims won the battle .There were fewer casualties ,but among those who embraced shahada ,many were Hafiz e Quran .Observing this Hazrat Umar Farooq urged Hazrat Abu Bakar Siddique to take necessary action regarding preservation of Holy Quran .All of the great companions agreed upon the decision .They formulated a strategy compilation .Every person has to visit the committee of the assemblage with the evidence of the verses they had got. They must bring two witnesses to the authenticity of the text. Hazrat Zaid bin Sabit had no written proof of verses. He had only in his memory. This research study has mainly been tried to bring the similarities and dissimilarities of Siddique and Usmani era on the modern Islamic times to evaluate the compilation of Holy Quran. This analytical discourse provides the in-depth knowledge for both Holy Era’s that needs to be brought into the limelight.